THE EFFECT OF SELF-CONCEPT AND FAMILY SUPPORT ON STUDENT CAREER MATURITY - Salsabila Arsih; Firman - (INNOVATIO: Journal for Religious Innovations Studies, 2023)
Career maturity includes things that cannot be separated in the development stage. students who do not have career maturity will cause obstacles in the development process. Low career maturity results in doubts in determining a career, including both in determining employment and education. Students with a healthy self-concept will have career maturity or career goals. Students who receive family support will have positive thoughts even in difficult situations until they reach career maturity. The family has an important role in providing support for family members, including in terms of increasing understanding of their careers. This study aims to analyze the relationship between self-concept and family support on students' career maturity. The type of research used is library research, collecting data using books, journals and research sources related to the relationship between self-concept and family support on student career maturity. In order for students to achieve career maturity, the counseling teacher or counselor has the role of providing counseling service assistance that suits the needs of students. Abstrak: Kematangan karir termasuk hal yang tidak dapat dipisahkan dalam tahap perkembangan. siswa yang tidak memiliki kematangan karir akan menimbulkan hambatan dalam proses perkembangannya. Kematangan karir yang rendah mengakibatkan keraguan dalam menentukan karir, termasuk juga dalam menentukan pekerjaan maupun pendidikan. Siswa dengan konsep diri yang sehat akan memiliki kematangan karir atau tujuan karir. Siswa yang mendapat dukungan keluarga akan memiliki pikiran positif meskipun dalam situasi yang sulit hingga mencapai kematangan karir. Keluarga memiliki peran penting dalam memberikan dukungan bagi anggota keluarganya, termasuk dalam hal meningkatkan pemahaman terhadap karirnya. Penelitian ini bertujuan untuk menganalisis hubungan antara konsep diri dan dukungan keluarga terhadap kematangan karir mahasiswa. Jenis penelitian yang digunakan adalah penelitian kepustakaan, mengumpulkan data dengan menggunakan buku-buku, jurnal dan sumber-sumber penelitian yang berkaitan dengan hubungan konsep diri dan dukungan keluarga terhadap kematangan karir siswa. Agar siswa dapat mencapai kematangan karir, maka guru BK atau konselor berperan memberikan bantuan layanan konseling yang sesuai dengan kebutuhan siswa. Kata kunci: Konsep Diri, Dukungan Keluarga, Kematangan Karir.